Categories in Evaluation of Innovative Activities of Competing Firms - GENG, Xuesong (Institutional Knowledge at Singapore Management University, 2009)
I examine how the stock market evaluation of a firm’s innovative activities is influenced by the categorization of the firm and its rivals. I find that innovations that blur the industry boundaries cause negative evaluation bias, but the competing innovations by outside industry firms cause positive evaluation bias in firm valuation.